Effects of Fe2+ and Fe3+ ratio impregnated onto local commercial activated carbon coconut shell powder on the dye removal efficiency - Machdar, Izarul; Faradillasari, Cut; Khair, Nurul Atika; Asnawi, Teku Muhammad; BC, Alfiansyah Yulianur; Yunardi, Y (Institution for Industrial Research and Standardization of Industry - Padang, 2018)
The present study reports the performance of magnetic activated carbon impregnated with Fe2+ and Fe3+ on the removal of dye from a simulated wastewater. The magnetic activated carbon (MAC) as a magnetic absorbent was prepared by co-precipitation method and followed by impregnation process. The activated carbon (AC) was supplied from a local commercial activated carbon coconut shell powder. The objective of this study was to investigate the effects of Fe2+ and Fe3+ on the quality product of MAC for dye (methylene blue) adsorption. The molar ratios of Fe2+ and Fe3+ used during the preparation of the MAC were 1:1; 1:2, and 2:1. The MAC products were characterized by using scanning electron microscope (SEM), energy dispersive X-ray (EDX), and Fourier transform infrared spectroscopy (FT-IR) analysis techniques. The results confirmed that the concentration of magnetic particles (Fe3O4) on the MAC surface increased following the impregnation process. However, this results lowering adsorption properties of the MAC adsorbents, which subsequently affected the dye removal performance. The ratio of Fe2+:Fe3+ on the MAC preparation did not significantly change the MAC absorbent on the dye removal efficiency. Additionally, MAC derived from local AC possess a prospect as a sustainable alternative for dye pollutant adsorbent.AbstrakPenelitian ini melaporkan kinerja karbon aktif bersifat magnet yang di impregnasi dengan Fe2+danÂ Fe3+ dalam penyerapan zat warna dari air limbah buatan. Karbon aktif bersifat magnet (MAC) dibuat melalui metode co-presipitasi dan diikuti dengan proses impregnasi. Material karbon aktif (AC) dibuat dari tempurung kelapa yang diperoleh dari pasar lokal. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh ratio dari Fe2+ and Fe3+ terhadap kualitas produk MAC yang digunakan nantinya di dalam proses penyerapan zat warna (metilen biru). Rasio molar dari Fe2+ and Fe3+ yang digunakan di dalam penelitian ini untuk menghasilkan MAC adalah 1:1; 1:2, dan 2:1. Produk MAC yang dihasilkan dipelajari karakteristiknya melalui scanning electron microscope (SEM), energy dispersive X-ray (EDX), dan Fourier transform infrared spectroscopy (FT-IR). Dari hasil penelitian yang diperoleh dapat dikonfirmasi bahwa konsentrasi partikel-partikel magnet (Fe3O4) pada permukaan MAC meningkat setelah proses impregnasi. Walaupun demikian, hal ini menyebabkan turunnya kemampuan adsorbsi dari adsorben MAC. Perbandingan rasio Fe2+ and Fe3+ tidak secara nyata mempengaruhi efisiensi penyerapan zat warna. Adsorben MAC dari karbon aktif lokal memiliki potensi sebagai bahan alternatif ramah lingkungan untuk penyerap zat warna.